Digital Infrastructure Determinants of SPBE Implementation Effectiveness: Evidence from the North Kalimantan Provincial Government - Imelda imelda; Emha Taufiq Luthfi (SISTEMASI, 2026)
The implementation of the Electronic-Based Government System (SPBE) has become a key strategy for digital government transformation in Indonesia. However, its effectiveness remains influenced by various aspects of digital infrastructure that are not yet fully optimized, particularly in geographically challenging regions such as North Kalimantan Province. The implementation of SPBE in North Kalimantan Province has demonstrated a substantial improvement in its SPBE index over the past five years. Despite this continuous increase, limited empirical research has examined the contribution of individual digital infrastructure dimensions to the effectiveness of SPBE implementation. This study aims to analyze the effects of network infrastructure, IT resources, information security, and government system integration on the effectiveness of SPBE implementation in North Kalimantan Province. A quantitative approach was employed using 20 research indicators and 20 questionnaire items, with data collected from 75 respondents through a census sampling technique. The data were analyzed using multiple linear regression. The descriptive statistical results indicate that information security had the highest mean score, whereas IT resources had the lowest mean score among the variables examined. The multiple regression analysis shows that network infrastructure, IT resources, information security, and government system integration significantly affect SPBE effectiveness, both individually and simultaneously. Network infrastructure was identified as the most dominant determinant (β = 0.361; p < 0.001), while the regression model explained 97.0% of the variance in SPBE effectiveness (Adjusted R² = 0.970). Based on these findings, the study recommends accelerating the equitable development of digital infrastructure and providing continuous training for IT personnel to improve the effectiveness of SPBE implementation. The findings provide practical guidance for the North Kalimantan Provincial Government to strengthen SPBE implementation by accelerating digital infrastructure development, particularly in remote areas with limited network coverage, while enhancing the capacity and availability of qualified IT resources.